“Control interno en la cooperativa de transporte Rio San Pablo del cantón La Maná, provincia de Cotopaxi, en el año 2019”. - Jimenez Alcivar, Madelin Estefania (2020)
The present investigation was carried out at the Río San Pablo Transport Cooperative located at Av. Amazonas and San Pablo. This research arises with the problem of evaluating the internal control system in the institution and determining the efficiency and effectiveness of those controls. The main specific objectives of the research are: to evaluate the internal control system and to design an improvement proposal to reduce the risks to which the cooperative is exposed. Based on the topic, the inductive methods that were used throughout the development of the theoretical framework were applied. The deductive method allowed to obtain important data to know the state of the cooperative and analytical in which the records and accounting documents were analyzed. In addition, two approaches were applied, the quantitative approach in which clearly specific questions were asked in the surveys, qualitative approach allowed to describe details of situations, events, people, interactions, observed behaviors; observation, interview, and survey techniques were also applied. With the survey carried out, it was possible to determine that 72% of the respondent’s state that there has not been an evaluation of the internal control of the cooperative and while 58% of users affirm that the evaluation of the internal control system is necessary.